FROM STATE ISLAMIC INSTITUTE TO STATE ISLAMIC UNIVERSITY: INSTITUTIONAL COMMUNICATION, REBRANDING, AND REPUTATION FORMATION AT IAIN KEDIRI - Siti Amanah; Singgih Muflihhafiz Labibah (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2026)
The transformation of IAIN Kediri into a State Islamic University (UIN) requires an effective institutional communication strategy to build a positive image and credible reputation in the eyes of the public. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation, involving campus leaders, the Public Relations team, and the community as key informants. The results show that IAIN Kediri implements an integrated communication strategy through internal (students, lecturers, educational staff) and external (community, alumni, partners) audience mapping via forums, surveys, social media, and direct interaction, the formulation of informative and inspiring messages, and the optimal use of digital media (social media, websites, and official publications) and public activities. The Public Relations Team serves as the frontline in branding and publicity, forming a cross-unit task force to ensure message consistency and strengthen the institution's image. The implementation of this strategy has significantly impacted public understanding, strengthened community trust, and enhanced the institution's exposure and reputation during the transformation process into UIN Syekh Wasil Kediri.